Problematika Guru dalam Pemanfaatan Media Pembelajaran Inovatif pada Mata Pelajaran SKI - Jihan Fika Mafaza; Anita Puji Astutik (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to determine the problems of SKI teachers in using learning media in the classroom. Learning media is an intermediary that can facilitate teachers during the learning process and help in delivering material to students. The use and development of learning media has become a must for every teacher because learning media can increase student understanding, motivate to be enthusiastic about learning, and attract student attention. This research method uses descriptive qualitative. Data collection techniques using observation, interviews and documentation. The results of the study indicate that the utilization of learning media in MTs Nurus Syafi'i with SKI subjects is still not optimal, due to limited school facilities, lack of routine checks by the principal on teacher discipline in making RPP, lack of availability of human resources and teacher knowledge in planning learning media that are in accordance with the subject matter. In general, the utilization of learning media by SKI teachers at MTs Nurus Syafi'i is by searching for references on the internet and then displaying them on an LCD projector.